Short‐range and long‐range order of phyllomanganate nanoparticles determined using high‐energy X‐ray scattering. (18th January 2013) - Manceau, Alain; Marcus, Matthew A.; Grangeon, S.; Lanson, M.; Lanson, B.; Gaillot, A.‐C.; Skanthakumar, S.; Soderholm, L.
<x xml:space="preserve">Abstract</x> High‐energy X‐ray scattering (HEXS) is used to explore the pH‐dependent structure of randomly stacked manganese oxide nanosheets of nominal formula δ‐MnO2. Data are simulated in real space by pair distribution function (PDF) analysis and in reciprocal space by both the Bragg‐rod method and the Debye equation in order to maximize the information gained from the total scattering measurements. The essential new features of this triple‐analysis approach are (1) the use of a two‐dimensional supercell in PDF modeling to describe local distortions around Mn layer vacancies, (2) the implementation in Bragg‐rod calculations of a lognormal crystal size distribution in the layer plane and an empirical function for the effect of strain, and (3) the incorporation into the model used with the Debye equation of an explicit elastic deformation of the two‐dimensional nanocrystals. The PDF analysis reveals steady migration at acidic pH of the Mn atoms from layer to interlayer sites, either above or below the Mn layer vacancies, and important displacement of the remaining in‐layer Mn atoms toward vacancies. The increased density of the vacancy–interlayer Mn pairs at low pH causes their mutual repulsion and results in short‐range ordering. The layer microstructure, responsible for the long‐range lateral disorder, is modeled with spherically and cylindrically bent crystallites having volume‐averaged radii of 20–40 Å. The b unit‐cell parameter from the hexagonal layer has different values in PDF, Bragg‐rod and Debye equation modeling, because of the use of different weighting contributions from long‐range and short‐range distances in each method. The PDF b parameter is in effect a measure of the average inlayer Mn...Mn distance and consistently deviates from the average structure value determined by the Bragg‐rod method by 0.02 Å at low pH, as a result of the local relaxation induced by vacancies. The layer curvature increases the Bragg‐rod value by 0.01–0.02 Å with the cylindrical model and as much as 0.04–0.05 Å with the spherical model. Therefore, in principle, the diffraction alone can unambiguously determine with good accuracy only a volume‐averaged apparent layer dimension of the manganese oxide nanosheets. The b parameter is model dependent and has no single straightforward interpretation, so comparison of b between different samples only makes sense if done in the context of a single specified model.